Com o pé na África: corpo, arte e lazer em um terreiro de candomblé - Genesco Alves de Sousa (2021)
The current study deals with the process of immersion in an “candomblé community” located in the metropolitan region of Belo Horizonte (Minas Gerais – Brazil), approached as a context of cultural experiences capable to intertwining different ways of life, cosmoperceptions, intersubjective relations, knowledge and specific social practices. Versions elaborated by the members of this community regarding their own experiences in this context, and the richness that emerge from them, were taken as starting point for articulating dialogues involving different fields of knowledge, giving the study of these experiences a markedly interdisciplinary character. In this approach, which focuses on the subjects and their daily interactions, contributions were received especially from the universes of anthropology, art, education and leisure studies. This work is, therefore, an ethnographic proposition that intends to broaden the debate about certain cultural manifestation of African origins in Brazil, even proposing other possibilities of approximation and understanding related to its current configurations.